The Concept of Pragmatics in Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Pragmatics studies the functional use of linguistic signs in speech. Pragmalinguistics is a scientific discipline that studies the relationship between speech and words, as well as the influence of language on understanding and perception of the world. The article examines the concept of pragmatics in linguistics.